210k views
0 votes
-12 = -5(x - 3) ......​

2 Answers

4 votes

Answer:

3.4

Explanation:

-12=-5(x-3)

destrubute

-5(x)--5(3)=-12

-5x + 15=-12

-15=-15

-5x=-17

x=-17/-5

x=3.4

User Axl
by
5.4k points
1 vote

Answer:

x = 27/5

Explanation:

Step 1: Write equation

-12 = -5(x - 3)

Step 2: Solve for x

  1. Distribute -5: -12 = -5x + 15
  2. Subtract 15 on both sides: -27 = -5x
  3. Divide both sides by -5: x = 27/5

Step 3: Check

Plug in x to verify it's a solution.

-12 = -5(27/5 - 3)

-12 = -5(12/5)

-12 = -12

User Tfv
by
5.2k points